News media translation - Zanettin, Federico (Cambridge CUP, 2021)
"As digital convergence marks the transition from print to screen culture, translation plays an increasingly important role of in the production and dissemination of the news. The translation of information in the news media is a pervasive set of practices that affects the daily consumption of the news and a topic of relevance to scholars in several areas of the humanities and the social sciences. This book provides a wide-ranging and accessible introduction to research in news media translation practices, products and processes, illustrating and discussing historical, theoretical and descriptive perspectives. Inter- and multidisciplinary research spans fields such as Translation Studies, Linguistics, Journalism and Media Studies, and includes approaches from Critical Discourse Analysis and narrative theory to Systemic Functional Linguistics and corpus linguistics. The book also offers first-hand analyses of news texts in English and Italian, approaching news translation from an ethnomethodological perspective"--
Includes bibliographical references and index.
Keywords: Journalism; Journalism -- Case studies; Translating and interpreting; Mass media and language; LANGUAGE ARTS & DISCIPLINES / Linguistics / General